Enteral formula compared to Nissen-Fundoplication: Data from a retrospective analysis on tolerance, utility, applicability, and safeness in children with neurological diseases - Trovato, Chiara Maria; Capriati, Teresa; Bolasco, Giulia; Brusco, Carla; Santariga, Emma; Laureti, Francesca; Campana, Carmen; Papa, Valentina; Mazzoli, Bianca; Corrado, Silvia; Tambucci, Renato; Maggiore, Giuseppe; et al. (Frontiers in Nutrition, 2023)
Approximately 46%-90% of children with neurological disorders suffer from gastrointestinal diseases, such as gastro-esophageal reflux disease (GERD), constipation or malnutrition. Therefore, enteral feeding is often necessary to achieve the nutritional requirements. The treatment of GERD could be based on pharmacological therapy, on nutritional treatment (changing type of formula) or on surgical treatment (Nissen Fundoplication, NF). We aimed to evaluate the effect of different enteral formulas compared to NF, with respect to tolerance, utility, applicability and safeness. Methods: We performed a retrospective analysis on all children with neurological damage (age: 29 days-17 years) treated from January 2009 to January 2019 due to nutritional problems and food and/or gastrointestinal intolerances. For all patients, demographic and anthropometric characteristics, symptoms, type of nutrition (formula and enteral access) and number and type of outpatient or emergency room visits were collected. Patients with less than 24 months of age at the closing of the database and with less than 12 months of observation were excluded. Results: From 376 children, 309 children (M: 158; median age: 4 IQR 1-10) were enrolled, among which 65 patients (NF-group M: 33; median age: 5.3 IQR 1.8-10.7) underwent NF. Vomit, GERD and dysphagia were more represented in NF-group (p<0.05). Our analysis shows that the NF-group seems to present a lower number of hospitalization and a lower number of visit for non-GI disorders, but a higher number of visit for GI disorders compared to non-NF. In the NF-group, higher prevalence of use of amino-acid based formula and free diet is observed, with a trend for lower prevalence of casein-based or whey+casein-based formula (Fisher test p=0,072). The median cost of a patient enrolled in the database is € 19,515 (± 540) per year, with no significant difference in the two groups. Concerning formula, at baseline, 76 children consumed free-diet, 24 casein-based, 139 whey+casein-based, 46 whey-based, 24 amino-acid based formula. Conclusions: In conclusions, compared to EN, NF may not improve clinical aspect and related cost in children with neurological disorders. Considering the psychological and QoL burden for patients, in a “step-up” strategy, EN could be proposed as an efficient alternative to NF.